Potential Bidirectional Relationship Between Periodontitis and Alzheimer’s Disease - Liccardo, Daniela; Marzano, Federica; Carraturo, Federica; Guida, Marco; Femminella, Grazia Daniela; Bencivenga, Leonardo; Agrimi, Jacopo; Addonizio, Armida; Melino, Imma; Valletta, Alessandra; Rengo, Carlo; Ferrara, Nicola; et al. (Frontiers in Physiology, 2020)
Alzheimer's disease (AD) is the most prevalent form of dementia in the elderly population, representing a global public health priority. Despite a large improvement in understanding the pathogenesis of AD, the etiology of this disorder remains still unclear, and no current treatment is able to prevent, slow, or stop its progression. Thus, there is a keen interest in the identification and modification of risk factors and novel molecular mechanisms associated with the development and progression of AD. In this context, it is worth noting that several findings support the existence of a direct link between neuronal and non-neuronal inflammation/infection and AD progression. Importantly, recent studies are now supporting the existence of a direct relationship between periodontitis,a chronic inflammatory oral disease, and AD. The mechanisms underlying the association remain to be fully elucidated; however, it is generally accepted, although not confirmed, that oral pathogens can penetrate the bloodstream inducing a low-grade systemic inflammation that negatively affects brain function. Indeed, a recent report demonstrated that oral pathogens and their toxic proteins infect the brain of AD patients. For instance, when AD progresses from early to more advanced stages, patients could no longer be able to adequately adhere to proper oral hygiene practices, thus leading to oral dysbiosis that, in turn, fuels infection, such as periodontitis. Therefore, in this review, we will provide an update on the emerging (pre-clinical and clinical) evidence that supports the relationship existing between periodontitis and AD. More in detail, we will discuss data attesting that periodontitis and AD share common risk factors and similar hyper-inflammatory phenotype.